Analisis Yuridis Pembatasan Pemberian Hak Milik Atas Tanah Untuk Rumah Tinggal: Juridical Analysis of Limiting Land Size for Residential Housing - Fitriana, Dina; Herlindah; Wicaksono, Setiawan (Faculty of Law, Universitas Brawijaya, 2023)
The restriction of the land size for residential housing is intended to prevent any piling up lands for certain people as in line with Articles 7 and 17 of Basic Agrarian Law (UUPA) which are further highlighted in Government Regulation according to Article 12 of Government Regulation in Lieu of Law Number 56 of 1960. However, there are no regulations governing the limitation of land size in place. More specific regulations regarding the right to land are outlined in the Decree of Agrarian Minister/the Head of National Land Agency Number 6 of 1998 concerning Grant of Right to Land for Residential Housing. The regulatory provisions highlight the restriction of the land size requested for residential housing and the land size that applicants can own, but it is only restricted to the applicants or for extended rights. The Decree of Agrarian Minister/the Head of National Land Agency Number 6 1998 does not seem to give a solution to what has been mandated in ownership or right restriction of non-agricultural lands, which is to be regulated in Government Regulation. Departing from the issue above, this research aims to study the grant of the right to land for residential housing by conducting a juridical analysis. This research use normative methods to analyze land ownership limitation and land registration.